Review The Utilization Of Video Games As A Learning Media For Islamic Religious Education - Prayogi, Arditya; Isbah, Faliqul; Ali, Fachri (Edification Journal : Pendidikan Agama Islam, 2023)
The use of video games in Islamic religious education is currently still not widely practiced. This is due to the idea that video games cannot be used as learning media because of their tertiary nature. This article then aims to present theoretical and practical studies on how to use and utilize video games as a medium in learning PAI. This article was compiled using a qualitative approach supported by data collection methods in the form of literature studies. From the results of the study, it was found that theoretically video games can be used in PAI learning seen from their role as a medium for transferring information and values, which can then be realized practically in several ways, including building the entire video game system, interpreting values in video games, and collaboration with various other media.